L'aspect linguistique des fusions-acquisitions d'entreprises - Vecchi, Dardo Mario de (2003)
In the business world, mergers can also be seen as the joining of two or more "company-speaks". Contrasts between different "speaks" are brought out when the communities are together and this can be observed in the spoken and written language. This situation can be compared to that of languages in contact from the sociolinguistic and dialectological points of view. Terminology offers an adapted perspective on descriptive, historical and cultural levels.
Dans le monde économique, les fusions-acquisitions impliquent aussi le regroupement des parlers des entreprises qui fusionnent. Les contrastes entre ces différents parlers deviennent manifestes lors du regroupement et apparaissent tant à l'oral qu'à l'écrit. La situation est comparable à celle de deux langues en contact, tant du point de vue sociolinguistique que du point de vue dialectologique. La terminologie offre des perspectives d'analyse pertinentes au niveau des composantes descriptives et de la traçabilité historique et culturelle de ces parlers.
Keywords: Company; Mergers; Company-speak; Terminology; Socioterminologie; Sociolinguistics; Dialectology; Entreprise^lfr; Fusion-acquisition; Parler d'entreprise; Terminologie; Socioterminologie; Sociolinguistique; Dialectologie; Sociolingüística